Management of COVID-19-Positive Pediatric Patients Undergoing Minimally Invasive Surgical Procedures: Systematic Review and Recommendations of the Board of European Society of Pediatric Endoscopic Surgeons - Pini Prato, Alessio; Conforti, Andrea; Almstrom, Markus; Van Gemert, Wim; Scuderi, Maria G.; Khen-Dunlop, Naziha; Draghici, Isabela; Mendoza-Sagaon, Mario; Giné Prades, Carlos; Chiarenza, Fabio; Steyaert, Henri (Frontiers in Pediatrics, 2020)
INTRODUCTION – Hospital response to the COVID-19 outbreak has involved the cancellation of elective, deferrable surgeries throughout Europe in order to ensure capacity for emergent surgery and a selection of elective but non-deferrable surgeries. The purpose of this document is to propose technical strategies to assist the pediatric surgeons to minimize the potential aerosolization of viral particles in COVID-19 patients undergoing urgent or emergent surgical treatment using laparoscopic approaches, based on the currently available literature. The situation and recommendations are subject to change with emerging information. MATERIALS AND METHODS – The Scientific Committee and the Board of the European Society of Pediatric Endoscopic Surgeons gathered together in order to address the issue of minimally invasive surgery during this COVID-19 pandemic. A systematic search through PubMed, Embase and World Wide Web of the terms “COVID-19”, “Coronavirus” and “SARS-CoV-2” matched with “pneumoperitoneum”, “laparoscopy”, “thoracoscopy”, “retroperitoneoscopy”, and “surgery” was performed. Non-English language papers were excluded. A PRISMA report was performed. Criticalities were identified and a consensus was achieved over a number of key aspects. RESULTS – We identified 121 documents. A total of 11 full-text documents were assessed to address all concerns related to the adoption of minimally invasive surgery. All aspect of pediatric minimally invasive surgery, including elective surgery, urgent surgery, laparoscopy, thoracoscopy, retroperitoneoscopy, and pneumoperitoneum creation and maintainance were extensively addressed through systematic review. A consensus regarding urgent laparoscopic procedures, setting and operation techniques was obtained within the Committee and the Board. CONCLUSIONS – The ESPES proposes the following recommendations in case minimally invasive surgery is needed in a COVID-19 positive pediatric patients: 1) consider conservative treatment whenever safely possible, 2) dedicate a theatre, columns and reusable laparoscopic instrumentation to COVID-19 pediatric patients, 3) prefer disposable instrumentation and cables, 4) use low CO2 insufflation pressures, 5) use low power electrocautery, 6) prefer closed-systems CO2 insufflation and desufflation systems, and 7) avoid leaks through ports. These recommendations are subject to change with emerging information and might be amended in the near future.